Critical Aspects in the Preparation of Extemporaneous Flecainide Acetate Oral Solution for Paediatrics - Antonella Casiraghi; Giorgio Centin; Francesca Selmin; Claudia Picozzi; Paola Minghetti; Davide Zanon (MDPI AG, 2021)
The availability of liquid oral preparations compounded by pharmacists is essential to meet paediatric needs which remain unanswered by the pharmaceutical industry. Unfortunately, compendial monographs are often not available and, in many cases, pre-formulation studies (e.g., compatibility with other excipients and solubility evaluations) are not performed in-depth, leading, in some rare cases, to the inadvertent administration of a toxic dose. In this study, the preparation of an oral liquid formulation for paediatric use, containing flecainide acetate at different strengths, was considered, taking into account the possible effects of conventionally used excipients. First, the optimal vehicle was selected based on a solubility study, evidencing some unexpected formations of precipitates. As a matter of fact, the buffers commonly used for oral solutions significantly reduced flecainide solubility, and the concomitant presence of citrate buffer and methylparaben even caused the formation of non-resuspendable crystals. Then, chemical, physical, and microbiological stability were assessed. Solutions at strengths of 10 and 20 mg/mL flecainide acetate were stable up to 8 weeks when compounded by using a 40% sucrose solution as a vehicle. Microbiological data showed that the use of methylparaben was not necessary over this time period.